2016
DOI: 10.1111/apm.12600
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic and genetic changes in soft tissue sarcomas: a review

Abstract: Soft tissue sarcomas are a versatile group of tumors with a proposed origin from mesenchymal stem cells. During recent years, the molecular biologic mechanisms behind the histogenesis of these tumors have become clearer. In addition to translocations and other genomic changes, epigenetic mechanisms have been shown to be greatly involved in the histogenesis of sarcomas as well as other cancers. Even though the molecular mechanisms behind sarcomas appear to be more complex than previously expected, epigenetic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 102 publications
(199 reference statements)
0
7
0
Order By: Relevance
“…For example, if melanocytes were to be affected, this would result in a melanoma 37 . Likewise, if different mesenchymal cell types are impacted, it could lead to the development of LMS, UPS or MFS 38,39 . This model needs to be con rmed experimentally to prove its involvement in sarcoma's inception.…”
Section: Discussionmentioning
confidence: 99%
“…For example, if melanocytes were to be affected, this would result in a melanoma 37 . Likewise, if different mesenchymal cell types are impacted, it could lead to the development of LMS, UPS or MFS 38,39 . This model needs to be con rmed experimentally to prove its involvement in sarcoma's inception.…”
Section: Discussionmentioning
confidence: 99%
“…Various hypotheses including gene mutations, expression of metallothioneins (MT) and influenced neighboring tissues by the same carcinogen have been used to explain the simultaneous development of a GIST and other carcinomas [ 10 , 11 ]. It is worth noting that genetic changes and polymorphisms play an important role in the development of sarcomas [ 12 ]. Furthermore, there is emerging data on genetic polymorphisms associated with susceptibility to a wide range of neoplasms [ 13 , 14 ], which can be reasonably explained by genetic changes and polymorphisms.…”
Section: Discussionmentioning
confidence: 99%
“…For sarcomas, genetic variations including mutational changes, translocations and fusions, have been identified from ctDNA in liquid biopsy 50 , 51 . Correspondingly, epigenetics variations in sarcomas mainly encompass three types: DNA methylation, histone modification and non-coding RNA modifications 52 , 53 . To date, only circulating non-coding RNAs , mainly microRNAs, have been studied in sarcoma liquid biopsy samples 38 , 40 , 54 , 55 .…”
Section: Detection Methods For Ctnasmentioning
confidence: 99%
“…LMS commonly affects the uterus or retroperitoneum but also occurs throughout the body 164 . LMS presents with a highly complex karyotype with no specific mutations 52 , 165 . Therefore, liquid biopsy in LMS is rare, and a recent study by Hemming et al found that a higher level of ctDNA, including a panel of genes with copy number variations, detected by ultra-low-passage whole-genome sequencing was correlated with tumor size and tumor progression in LMS 166 .…”
Section: Detection Methods For Ctnasmentioning
confidence: 99%